UV Spectra Fingerprint and Multivariate Analysis Approach for Identification of the Species of Panax - Zhong, Gui; Li Zhao, Yan; Zhang, Ji; Shen, Tao; Bo Xiao, Yan; Zhong Wang, Yuan; Yu Zhang, Jin (Asian Journal of Chemistry, 2014)
The genus Panax plants are important herbal remedies and dietary supplements. Species identification and source authentication of this genus are important to ensure their safety and efficacy. The aim of this study to identify Panax japonicus var. major, Panax stipuleanatus, Panax pseudo-ginseng var. bipinnatifidus, Panax sp. and Panax notoginseng by the use of UV spectra fingerprint and multivariate analysis methods, such as hierarchical cluster analysis (HCA) and partial least squares discriminant analysis (PLS-DA). The proposed method could divide the five genus Panax species into four classes, in which the Panax sp. and Panax notoginseng have been got together. The result indicated that this method was able to discriminate the five genus Panax species and provided reference for quality evaluation of Chinese herbal medicine.